Integrating Culture in English Education: Impacts on Students’ Communicative Competence - Azmi Randu Farhani (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study examines the integration of culture in English education and its impact on students’ communicative competence in an English as a Foreign Language (EFL) context. Recognizing that language and culture are inseparable, the study aims to explore how cultural elements embedded in English instruction contribute to students’ ability to communicate appropriately and effectively. A qualitative research approach was employed, involving classroom observations, semi-structured interviews with teachers and students, and document analysis of instructional materials. The findings indicate that cultural integration enhances students’ sociolinguistic and pragmatic competence, improves their understanding of contextual language use, and increases motivation and engagement in classroom interaction. The results also highlight the central role of teachers in mediating cultural understanding, as well as challenges related to limited resources, time constraints, and insufficient teacher training. Overall, the study concludes that integrating culture in English education supports the development of communicative competence and should be explicitly incorporated into curricula and teaching practices to prepare learners for meaningful intercultural communication.